2007
DOI: 10.1016/j.ccr.2007.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Inducible FGFR-1 Activation Leads to Irreversible Prostate Adenocarcinoma and an Epithelial-to-Mesenchymal Transition

Abstract: Fibroblast Growth Factor Receptor-1 (FGFR1) is commonly overexpressed in advanced prostate cancer (PCa). To investigate causality, we utilized an inducible FGFR1 (iFGFR1) prostate mouse model. Activation of iFGFR1 with chemical inducers of dimerization (CID) led to highly synchronous, step-wise progression to adenocarcinoma that is linked to an epithelial-to-mesenchymal transition (EMT). iFGFR1 inactivation by CID withdrawal led to full reversion of prostatic intraepithelial neoplasia, whereas PCa lesions beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
232
1
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 268 publications
(248 citation statements)
references
References 45 publications
13
232
1
2
Order By: Relevance
“…Murine models overexpressing key components of developmental signaling pathways alone or with other genetic alterations can drive a phenotype reminiscent of late-stage prostate cancer (19)(20)(21)(22). Although these studies provide evidence of a relationship between stem-like qualities and an aggressive phenotype, no studies to our knowledge have shown a molecular relationship between aggressive prostate cancer and uncultured stem-like cells from the human prostate.…”
Section: Significancementioning
confidence: 79%
“…Murine models overexpressing key components of developmental signaling pathways alone or with other genetic alterations can drive a phenotype reminiscent of late-stage prostate cancer (19)(20)(21)(22). Although these studies provide evidence of a relationship between stem-like qualities and an aggressive phenotype, no studies to our knowledge have shown a molecular relationship between aggressive prostate cancer and uncultured stem-like cells from the human prostate.…”
Section: Significancementioning
confidence: 79%
“…The stromal expression and release of various FGFs are related to angiogenic and tumor-promoting effects. More specifi cally, studies in transgenic mice have linked FGFR1 activation and FGF8 epithelial overexpression to epithelial-mesenchymal transition and the induction of prostatic adenocarcinomas ( 47 ). A humanized monoclonal anti-FGF8 antibody and selective FGFR TKIs, such as AZ8010, …”
Section: Autocrine/paracrine Signalingmentioning
confidence: 99%
“…growth factor signaling). Among the growth factors known to induce EMT are transforming growth factor β (TGFβ) [3], hepatocyte growth factor (HGF) [4], members of the epidermal growth factor (EGF) family [5], insulin-like growth factor (IGF) [6], and fibroblast growth factor (FGF) [7,8]. Recently, also Notch signaling has been implicated in EMT in human breast cancer cells by activating the transcription factor Snail2 (Slug), a potent repressor of E-cadherin gene expression [9].…”
mentioning
confidence: 99%